Pelatihan Batik Shibori Pada Kelompok Belajar Binaan Karang Taruna “Rinjani Asri” - Siti Rabiatul Adawiyah; Intan Kusuma Wardani; Nofisulastri Nofisulastri; Fitri Astutik; Muhamad Sarifuddin (Puslitbang Sekawan Institute Nusa Tenggara, 2021)
Based on the results of the study, shibori batik can improve children's fine and gross motor skills because it’s interesting and not boring and has the goal of training the flexibility of the finger muscles, avoiding boredom, and as an alternative for psychological health first aid for disaster survivors, especially during the pandemic. covid 19. One of the phenomena of the impact of the pandemic, problems were found in the